Simulation data for tracing snowball bifurcation on an earth-like aquaplanet over 4 billion years - Feulner, Georg; Bukenberger, Mona Sofie; Petri, Stefan (GFZ Data Services, 2022)
Abstract The atmospheric concentration of CO2 at which global glaciation (snowball) bifurcation occurs, changes throughout Earth's history, most notably because of the slowly increasing solar luminosity. Quantifying this critical CO2 concentration is not only interesting from a climate dynamics perspective, but also an important prerequisite for understanding past Snowball Earth episodes as well as the conditions for habitability on Earth and other planets. Here we use the coupled climate model CLIMBER-3α in an Aquaplanet configuration to scan for the Snowball bifurcation point for time slices spanning the last 4 billion years, thus quantifying the time evolution of the bifurcation and identifying a qualitative shift in critical state dynamics. Methods To scan for the Snowball bifurcation for more than a dozen time slices throughout Earth’s history, we use the relatively fast Earth-system model of intermediate complexity CLIMBER-3α. It consists of a modified version of the ocean general circulation model (OGCM) MOM3 with a horizontal resolution of 3.75◦× 3.75◦ and 24 vertical levels, a dynamic/thermodynamic sea-ice model the same horizontal resolution and a fast statistical-dynamical atmosphere model with a coarse horizontal resolution of 22.5◦ in longitude and 7.5◦ in latitude. The sea-ice model explicitly takes into account sea-ice dynamics, a factor which has been found to be of crucial importance for the Snowball bifurcation. The effects of snow cover on sea ice are explicitly taken into account. The main limitations of the model relate to its simplified atmosphere component. For more details see the corresponding paper.